Innovation in work-based doctoral learning: initial findings and observations from the Prince of Wales Innovation Scholarship Programme and its new Pedagogies - Louisa Huxtable-Thomas (Proceedings of the 4th International Conference on Education, Research and Innovation (ICERI) 2011)
This paper outlines a model of work-based learning for PhD scholars - introducing the concept of 'scholagogy' and extrapolates a higher level of successful PhD completions than average for the UK in comparison with models utilised in Germany and Australia.